Cloud-Based Remote Sensing with Google Earth Engine Fundamentals and Applications (Cham Springer Nature, 2024)
This book guides its audience-which can range from novice users to experts- though a 55-chapter tour of Google Earth Engine. A sequenced and diverse set of lab materials, this is the product of more than a year of effort from more than a hundred individuals, collecting new exercises from professors, undergraduates, master's students, PhD students, postdocs, and independent consultants. Cloud Based Remote Sensing with Google Earth Engine is broadly organized into two halves. The first half, Fundamentals, is a set of 31 labs designed to take the reader from being a complete Earth Engine novice to being a quite advanced user. The second half, Applications, presents a tour of the world of Earth Engine across 24 chapters, showing how it is used in a very wide variety of settings that rely on remote-sensing data This is an open access book.
English
Keywords: Algorithms & data structures; Analytical chemistry; Artificial intelligence; Computer vision; Environmental monitoring; Imaging systems & technology